A narrative literature review on the impact of social media use as marketing tools for enhancing micro, small & medium enterprises (MSMEs) business performance in Malaysia / Nur Ainul Basyirah Amran - Amran, Nur Ainul Basyirah (Faculty of Communication and Media Studies (FCMS), 2023)
In today’s digital age, social media has become an avenue where MSMEs can extend their marketing campaigns to a wider range of consumers. This study aims to understand the impact of social media use as marketing tools for enhancing MSMEs business performance in Malaysia. This study based on qualitative data obtained through a narrative literature review involving gathering, critiquing and summarising journal articles textbooks related to the research topic. The data drawn from ten selected journal articled identified using Google Scholar, covering the period from 2019 to 2023. The findings of this study reveal consistent impacts of social media use, emphasizing the dependence on industry type and the specific social media platforms aligned with MSMEs' business objectives. The results of this study indicate that the use of social media for marketing has a positive effect on the performance of MSMEs, especially in increasing sales, customer relationships, productivity, and creativity. This means that the better the use of social media for marketing, the better the performance of MSMEs will be. Nonetheless, the impact of this study is still widespread. Therefore, further research needs to be done to gain more insights on the drivers of social media use and their impact on the performance of MSMEs.